If You Build it, Will They (Really) Come? Student Perceptions of Proximity and Other Factors Affecting Use of an Academic Library Curriculum Collection - Vanderwerff, Madelaine; Herscovitch, Pearl (Evidence Based Library and Information Practice)

(untitled) (University of Alberta Library, 2021)
Objective – This study investigated student perceptions of an undergraduate university library’s curriculum collection, before and after a move to a new library building. The objective was to identify how factors such as proximity to program classrooms and faculty offices, flexible seating, accessibility, and other physical improvements to the space housing the collection impacted students’ perceptions.Methods – This longitudinal study conducted between 2016 and 2017 used a combination of methods to examine whether library use of a specialized academic library collection was impacted by a significant space improvement and change in location. A cohort of education students was surveyed before and after the construction of a new building that housed both the library and their department and co-located the curriculum collection with departmental teaching spaces. The students were surveyed about their use of the space and resources. The researchers then compared the survey results to circulation data. The researchers ground this study in Lefebvre’s spatial triad theory, applying it to library design and collection use (Lefebvre, 1992).Results – Researchers identified proximity to classrooms and general convenience as the dominant factors influencing students’ use of the collection. Survey results showed an increased awareness of the collection and an increase in use of the collection for completion of assignments and practicum work. Circulation data confirmed that between 2016-2019, there was a steady increase in use of the curriculum collection.Conclusion – Students’ responses revealed that physical characteristics of the space were less important than proximity, the major factor that impacted their use of the curriculum collection. This revelation confirms Lefebvre’s idea that spatial practice, i.e., how users access and use the space, is more significant and identifiable to students than the design and physical characteristics of the space.